Changing red blood cell transfusion practice in obstetrics and gynaecology: A before and after study of hospital‐wide education. Issue 1 (24th November 2021) - Thiel, Peter S.; Mah, Alicia C.; Siddiqui, Muhammad; Lett, Christine D.
Abstract: Objectives: To assess transfusion practices at a Canadian tertiary care center before and after a hospital‐wide blood management educational campaign based on the Choosing Wisely toolkit. Background: Red blood cell (RBC) transfusions are an essential intervention in obstetrics and gynaec ology (O&G). However, with limited guidelines outlining the appropriate use of RBC transfusions, clinicians routinely transfuse based on haemoglobin values and habits. Methods/Materials: We conducted a retrospective chart review of all patients who received a RBC transfusion while admitted under an O&G provider in two 12‐month periods—before and after the intervention. The campaign consisted of Grand Rounds, formal and informal teaching, and posters placed within the hospital. We judged appropriateness from a set of criteria guided by the status of ongoing bleeding, pre‐transfusion haemoglobin, and the number of units ordered simultaneously. Results: Transfusion appropriateness was poor in pre‐ and post‐intervention periods (46% vs. 51%, p  = 0.59). The overall rate of RBC transfusion was reduced from 1.8% to 1.2% (83/4610 vs. 55/4618, p  = 0.02) after the intervention. There was a 52% reduction in the total number of RBC units of transfused (229 vs. 111, p  < 0.001), a 33% reduction in the number of patients transfused (83 vs. 55, p  = 0.016), and fewer multiple‐unit transfusions without reassessment (39 vs. 13, p  = 0.005). Conclusion: RBC transfusion appropriateness remained low after a hospital‐wide educational campaign. However, there was a marked decrease in overall transfusion use, reflecting the adoption of more restrictive transfusion practices. The low rate of transfusion appropriateness represents an opportunity for further improvement.